Photoacoustic (pas) spectral measurements of Amorphous Silicon semiconductor films - Fernández Chillcce, Enver (1999)
In this work we present the results of the photoacustical (PAS) characterization of thin film amorphous silicon (a-Si:H). The optical parameters (n,k) are obtained for semiconductive films, obtained by a reactive “DC glow discharge” process by spectral Transmission and absortion PAS measurements in a great spectral range and good agreement with previous evaluations .We determine finally the quasi gap energy (Tauc) and the band model of the semiconductor of a-Si:H.